UJARAN ANAK PADA FASE HOLOFRASA FUNGSI, BENTUK & KONTEKS - Murny Murny (Sosial Budaya, 2011)
This Research discusses about the fungtions, forms, and contexs, of child's speech at the holophrastic stage. This subject of this resarch is a young boy (one year and eight month old) his name is M. Fakhrurrozi. The data are collected by tape recording and take note of the child's naturally occuring utterance. This resarch used qualitatif approach with descriptive method. Research finding suggest that: the fungtions of the utterances fall into three group, giving information(50%), statement(25%), and request(25%).Contexs help the researcher identifying of utterance (75%), two word utterance (25%), and three word utterance (2,5%). it was also found the child used incompleted utterance,and he used the last sylabel of the word more frequently.